Effect of Hyperbaric Oxygen Therapy on Peripheral Vascular Diseases - Spasojevic, Natalija; Brkić, Predrag (Medicinski podmladak, 2017)
Abstract Introduction Peripheral vascular disease (PVD) is a common and concerning symptom of several habits and illnesses and occurs most often in the lower extremities. PVD manifests itself by decreasing blood flow to tissues and therefore causing a lack of oxygenation, which, if not treated, can ultimately progress to ulcer formation. It is suggested that Hyperbaric oxygen therapy (HBOT) may lead to revascularization of affected tissue. Aim This study was performed in order to determine whether HBOT aids wound and ulcer healing, that were caused by PVD. Material and Methods 20 participants (14 male, 6 female and age ranging from 45 to 89) took part in this case study. All of them suffered from PVD symptoms, such as developed ulcers, open wounds and pain. At 2.2 atmospheres (ATM) with 100% oxygen, the patients fulfilled 15 sessions, each lasting 60 minutes of which the decompression and compression phases lasted each 10 minutes. Treatment took place in the Center for Hyperbaric Medicine in Belgrade. Existing ulcers and their changes were classified. The subjective feeling of pain was being routinely evaluated. The data were analysed with the student t-test and ANOVA. Results Outcome presented itself with a clear commenced healing of ulcers, wound and pain reduction. Additional improvements in elongation of intermittent claudication distance and peripheral sensation could also be observed. Ten patients partook in 5 or 10 further sessions before noteworthy progress could be observed. Conclusion According to this study, HBOT can facilitate the healing of existing ulcers and wounds caused by PVD if used as a preventative method. However, a larger amount of participants with control groups should be used for a definitive conclusion. Keywords: Peripheral vascular disease, hyperbaric oxygen therapy, ulcer